Bacterial diversity associated with a newly described bioeroding sponge, Cliona thomasi, from the coral reefs on the West Coast of India - Mote, Sambhaji; Gupta, Vishal; De, Kalyan; Nanajkar, Mandar; Damare, Samir R; Ingole, Baban (Folia microbiologica, 2021)
The bacterial diversity associated with eroding sponges belonging to the Cliona viridis species complex is scarcely known. Cliona thomasi described from the West Coast of India is a new introduction to the viridis species complex. In this study, we determined the bacterial diversity associated with C. thomasi using next-generation sequencing. The results revealed the dominance of Proteobacteria followed by Cyanobacteria, Actinobacteria and Firmicutes. Among Proteobacteria, the Alphaproteobacteria were found to be the most dominant class. Furthermore, at the genus level, Rhodothalassium were highly abundant followed by Endozoicomonas in sponge samples. The beta-diversity and species richness measures showed remarkably lower diversity in Cliona thomasi than the ambient environment. The determined lower bacterial diversity in C. thomasi than the environmental samples, thus, categorized it as a low microbial abundance (LMA). Functional annotation of the C. thomasi-associated bacterial community indicates their possible role in photo-autotrophy, aerobic nitrification, coupling of sulphate reduction and sulphide oxidization. The present study unveils the bacterial diversity in bioeroding C. thomasi, which is a crucial step to determine the functions of the sponge holobiont in coral reef ecosystem.
Keywords: Animals; India; ekosystém; Porifera; Ecosystem; zvířata; Indie; Bacteria; korálové útesy; Coral Reefs